Governance Challenges: Achieving Sustainable Development in Developing Countries - Marie, Ziyad (The Arab Journal of Administration, 2025)
The research focuses on the governance constraints that may be addressed to enable sustainable development in underdeveloped nations. The study focuses on five primary governance obstacles impeding progress: rule of law, political stability, the quality of laws and legislation, government performance, and corruption. Using a theoretical framework as the foundation for a thorough analysis, the researcher assesses the relevance of these issues and recommends solutions. The basic goal of this study is to propose country-specific methods that improve global cooperation between nations, particularly among immigrant populations; they should also be equitable and environmentally sustainable. The study’s analytical approach entails a thorough examination of each governance concern to assess its current condition and identify its core causes, and suggest possible remedies based on empirical evidence. The inadequacy of legal frameworks and political stability to handle these difficulties was also addressed, with the conclusion arguing for alternative ways that address underlying challenges such as poverty, inequality, and citizen involvement. The study highlighted effective government, an emancipated society, and legislation to combat corruption as critical components of sustainable development. Additional ideas include the need for a worldwide knowledge-sharing platform for international collaboration, country-specific roadmaps addressing unique difficulties faced by all developing countries, and the identification of best practices. It also supports tight monitoring and assessment processes to ensure the constant evaluation and adaptation of development initiatives. According to this research, commitment to learning opportunities remains necessary to promote ethical leadership values among developing countries while engaging with stakeholders in government business so they can operate more openly.